On the Study of Dmanisi Mineral Water, Georgia - Khazaradze , Natia; Omiadze, Khatuna (International Journal of Membrane Science and Technology, 2023)
The object of study is the Dmanisi Mineral Water in the municipality of Dmanisi in Georgia. Although water has been used for centuries to treat kidney diseases, it was studied for the first time.